Production and properties of shelf-stable spray-dried powder from enzyme-treated soursop (Annona muricata L.) fruit - Chang, Lee Sin (2017)
In Malaysia, the production of soursop (Annona muricata L.) fruit has increased dramatically due to a strong consumer demand because of its nutritional and health protective values. However, one of the apparent features of this fruit is that it softens easily after harvested due to a high respiration rate, and this leads to a short shelf life. Thus, in this study, fresh soursop fruit was preserved by spray-drying it into a shelfstable powder that may serve the food industry as a value-added intermediate product, and also in the health industry as a food supplement. In the first part of the study, commercially available enzyme preparations, Pectinex® Ultra SP-L (pectinase), Fungamyl® 800 L (α-amylase) and Celluclast® 1.5 L (cellulase) (Novozymes, Denmark), were used in a pre-treatment step to liquefy soursop mesocarp and 1.5 % (v/w) pectinase was selected as the primary enzyme because it produced soursop puree effectively. Besides, when pectinase was combined with cellulase, a liquefied puree with a significant (p ≤ 0.05) reduction of viscosity of up to 50 % within a shorter incubation time (75 minutes) was produced. Apart from determining many physicochemical properties such as pH, titratable acidity, total soluble solid, sugar, and organic acid profiles, the volatile compounds of soursop fruit and puree were compared using a zNose (Ultrafast GC, USA). Principal Component Analysis (PCA) results indicated six important volatile compounds generated the highest total variance (92.9 %) which classifies the aroma profiles into three groups: raw soursop fruit, soursop fruit treated with pectinase, and liquefied puree from combined enzyme treatment. Two ester compounds, namely methyl hexanoate and methyl trans-2- hexenoate, were identified as the major volatile compounds present in soursop. In an attempt to optimize the production conditions for soursop powder, Response Surface Methodology (RSM) was applied to study the effect of cellulase concentration (0 to 2 % v/w) at fixed pectinase concentration (1.5 % v/w), the addition of maltodextrin (20 to 40 % w/w), and spray-drying inlet temperature (130 to 160 ºC) on the properties of spray-dried soursop powder. Results showed that the polynomial model was significantly fitted (p ≤ 0.05) for process yield, moisture content, water activity, hygroscopicity, and stickiness. However, the bulk density, true density, porosity, particle size and water adsorption index did not fit significantly (p > 0.05) into the model. The color of the spray-dried soursop powder appeared slightly creamy, most probably due to the combination of soursop puree (cream) and maltodextrin (white). The glass transition temperature (Tg) was found to range between 46.53 and 58.25 °C, indicating the spray-dried soursop powder is an amorphous material. Surface morphology of powder, viewed by Scanning Electron Microscopy (SEM), showed that the particles exhibited the general morphology of amorphous powder: spherical shape and possessed a continuous wall (crust) without surface cracks. Based on multiple responses optimization of the process, puree that is pre-treated with 1.3 % (v/w) cellulase and incorporated with 37 % w/w maltodextrin and then spray-dried at an inlet temperature of 156 ºC may be transformed into soursop fruit powder that had optimal physicochemical properties. At the optimum spray drying conditions, the soursop powder obtained had residual stickiness when stored. Thus, the effect of addition of different types [tricalcium phosphate (TCP) and calcium silicate (CS)] and concentrations (0 - 1.5 % w/w) of anticaking agents, and storage temperatures (conventional storage at 25 ± 1 ºC and accelerated storage at 38 ± 1 ºC) on properties of the powder heat-sealed in aluminum laminated polyethylene (ALP) pouches was examined. Statistically, results showed the addition of either of the anticaking agent significantly (p ≤ 0.05) increased the process yield of powder. The physicochemical properties of the powder were also significantly (p ≤ 0.05) affected by the presence of an anticaking agent, and by storage time and temperature. The critical moisture content (Xc) for the powder was ranged from 0.069 to 0.072 g H2O/g ds. Kinetic modelling for color change (ΔE) showed zero order degradation reaction. The lowest kinetic constant was recorded for 1.5 % CS which had the highest activation energy (Ea) (17.26 kJ/mol), indicating powder added with CS had less tendency to undergo color change. Powder added with 1.0 % TCP or 1.5 % CS were optimal for the production of soursop powder, and for estimation of shelf life. Shelf life of powder optimized under the conditions obtained above was estimated based on the moisture sorption isotherm (MSI) of soursop powder which was determined gravimetrically. Results indicated that the equilibrium relative humidity (ERH), the type of anticaking agents, and storage temperatures had significant (p ≤ 0.05) effects on the equilibrium moisture content (EMC) of soursop powder. The Guggenheim, Anderson, and de Boer (GAB) model which was used to fit sorption data reflected a sorption curve which followed Type III Brunauer’s classification. The monolayer moisture content (Mo) of the powder varied from 0.0221 to 0.0243 g H2O/g ds. The longest shelf life was predicted for powder treated with 1.5 % TCP (316 days). Prediction of shelf life using the kinetic model was reasonably adequate as the calculated mean relative percent deviation modulus was less than 10 % (2.3 - 6.9 %). Hedonic test of five sensory attributes, namely aroma, color, mouthfeel, taste, and overall acceptability, for all reconstituted soursop drink showed mean scores that were higher than six from a maximum of nine, indicating high acceptability.Overall, the production of shelf-stable soursop powder was made possible by having a spray drying feed that was puree-like that had low viscosity due to enzymatic treatment of fruit pulp. Soursop powder produced by spray drying exhibited general properties and morphology of an amorphous powder. The addition of food additives demonstrated anticaking effect by reducing moisture adsorption of powder to prevent caking phenomenon. Both anticaking agents prolonged the shelf life of powders possibly by forming a protective barrier on the sample particle to improve powder stability over time.